Can engaging local people’s interests reduce forest degradation in Central Vietnam? - Boissiere, M.; Sheil, Douglas; Basuki, I.; Wan, M.; Le, H. (2009)
Governments in tropical countries are still responding to increasing forest degradation by implementing different types of protected areas. In general, due to their negative image as causes of deforestation, local communities are being excluded from any management role in these conservation areas. However, in Vietnam, since 1986 various incentives have been proposed for alternative conservation models. Our surveys used a multidisciplinary combination of methods to work with one Pahy ethnic minority around the degraded forests of the proposed Phong Dien Nature Reserve in Central Vietnam. From the results of these surveys we obtained clear indication that conservation can be enhanced if local priorities, perspectives and wishes are better identified and taken into account. The local communities identified the need for, at least, limited extractive activities in the protected area. They also frequently stressed their willingness to participate in the monitoring and control of the area, and in the selection of local species for reforestation programmes. Communities can and should be actively involved in building a shared understanding of what the forest provides, how it can be conserved and the benefits to be obtained. Conservation in Vietnam has much to gain from local participation. However, suitable safeguards and incentives need to be in place to insure sustainable use of the forest resources